Arctic Centre: Rovaniemi, Finland - William C. Miller; Gregory A. Yager (Oz, 1984)
The Arctic Centre, developed in response to the City of Rovaniemi's issuance of an ideas competition, is a complex incorporating two facilities: the Arctic Museum and the Lapland Provincial Museum…